2016
DOI: 10.1038/srep37987
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy induces fast tumor control and symptom relief in patients with iliac lymph node metastasis

Abstract: The CyberKnife is a robotic stereotactic body radiotherapy (SBRT) system which has shown promising results for many malignances with good efficacy and low toxicity. This study aims to evaluate the response and local control (LC) obtained with CyberKnife in the management of iliac lymph node metastases (ILNM). Twenty-two patients with 27 ILNM were treated by CyberKnife from May 2010 to May 2016. Median follow-up time was 33 months (8–97). The complete response, partial response, stable disease and progression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Local consolidative therapy, including radiotherapy or other ablative therapy, combined with systemic therapy could provide synergistic effects. This result was similar to previous studies about liver or iliac lymph node metastases 16,17,21 . Wang et al 17 analyzed the clinical efficacy of SBRT for iliac lymph node metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Local consolidative therapy, including radiotherapy or other ablative therapy, combined with systemic therapy could provide synergistic effects. This result was similar to previous studies about liver or iliac lymph node metastases 16,17,21 . Wang et al 17 analyzed the clinical efficacy of SBRT for iliac lymph node metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have reported clinical practices of SBRT for different metastases, including the lung, liver, iliac lymph node, brain and bone metastases [15][16][17] . Nevertheless, the efficacy of SBRT for AGM has been evaluated in only a few studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, stereotactic body radiotherapy (SBRT) limited to macroscopic lymphadenopathies has been investigated by a number of authors, reporting promising results in terms of 1-years local control > 90% [ 16 22 ], optimal symptom control [ 22 ], long systemic therapy-free interval [ 21 ] and the possibility to iteratively perform SBRT in case of limited secondary relapse [ 19 , 23 ]. Nevertheless, toxicity reports and lack of data regarding distant failure and impact on survival, raised doubts about the efficacy of this strategy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been some reports about SBRT for recurrent gynecological malignancies 13 15 and some reports about SBRT for pelvic lymph node metastases from various primary diseases, 16 as far as we know, there have been few review reports about particular cases of SBRT for recurrent lymph node metastasis from gynecological cancers. In 2009, Choi et al reported results of treatment for PALN metastases from uterine cancer.…”
Section: Gynecological Cancermentioning
confidence: 99%